Impact of Product Placement of Movies on Consumers Buying Behaviour - Balachandar S, Sheetal Mahendher, Nila A Chotai, Leonard L, M. Thouyangba Meetei (Journal of Informatics Education and Research, 2024)
The use of product placement in movies has become a popular marketing strategy to influence consumers' buying behaviour. The purpose of this research paper is to examine the impact of product placement in movies on consumers' buying behaviour. The research methodology employed a survey questionnaire distributed to a sample size of 50 respondents using Google Forms. The research findings indicate that product placement in movies has a significant impact on consumers' buying behaviour. The study concludes that product placement is an effective marketing tool that marketers can use to influence consumer behaviour.